(untitled) (Italian Journal of Public Health, 2009)
Strategic Management, Public Health Information, Public Health Legislation, as well as Public Health Training and Research are considered essential elements of a coherent public health strategy for Serbia, a republic of the former Yugoslavia. Whereas the strategic framework in Serbia is outlined in detail, which includes an action plan that is linked with local pilot initiatives, the information base is well developed but not yet sufficiently related to the strategic objectives. The transformation of strategic considerations and information into meaningful legislative acts stands at halfway and has to cope with a heritage of unrelated and dysfunctional laws. A big step forward was made with the establishment of a modern School of Public Health in Belgrade in 2004, which acts as a brain-trust for the New Public Health in Serbia. The multi-professionalism at the Institutes of Public Health and the corresponding inter-disciplinarity at the academic Schools of Public Health provide an adequate institutional environment if the resources of skills, knowledge and experience are adequately managed – in a participatory and supportive system representing a flat hierarchy.